Understanding predation of tortoises by nesting Pied Crows (Corvus albus) in western South Africa - Durà i Franch, Carles (Percy FitzPatrick Institute of African Ornithology, 2017)
Many species in a wide variety of taxonomic groups have shown shifts in their distribution ranges in recent decades. Rapidly changing distributions may lead to novel biotic interactions between species that have not historically interacted. As generalist predators, corvids are a potential threat to other species in areas where they have recently colonized or where their numbers have increased. Tortoise species appear to be one taxonomic group that may potentially suffer serious negative effects from increased corvid abundance. One species of corvid which has shown a significant range increase in the last two decades in western South Africa is the Pied Crow (Corvus albus). In conjunction with this expansion have come observed accounts of large numbers of tortoises being found depredated under Pied Crow nests, raising concerns over their impact on tortoises in these areas. Southern Africa has the richest biodiversity of tortoises in the world and a high rate of endemism. The endemic species are mainly restricted to the Cape region, where the genera Chersina, Homopus and Psammobates have their evolutionary centre. In this thesis, I explore how widespread tortoise predation by Pied Crows was during the crow's breeding season. I aimed to quantify the proportion of Pied Crow pairs that provision tortoise to their chicks and the numbers being depredated, as well as the species of tortoises involved. During the 2016 breeding season, I monitored 125 active Pied Crow nests in western South Africa. For the majority of these nests (n=93) there was no evidence for any tortoise predation. For the 32 pairs, where predation was recorded, I found that 15 pairs depredated ≤1 tortoise – week, five pairs depredated depredated between 1 and 2 tortoise–week , and 12 pairs depredated >2 tortoises–week. The tortoises prey remains found depredated depredated under Pied Crow nests had an average straight carapace length of 5.57 cm (range 3.5 cm - 9.8 cm) and 91% of them were Angulate Tortoises. Crows favour smaller tortoises with impacts for smaller species, or younger age classes. I also explored whether any environmental variables explained probability of tortoise predation or predation rates. Environmental variables examined included weather variables, land cover types, distances to roads and primary productivity values, and for a subset of nests the abundance of tortoises counted from transects. Although predation rate showed spatial variation among the study areas with most predation occurring in arid areas with high mean temperatures and low rainfall, no single environmental variable successfully predicted the variation in spatial predation.